Evaluation of Bawaslu Sidoarjo’s Recommendatory Authority inHandling Village Head Neutrality Violations in the Perspective ofBridgman and Davis Theory - Nur Aini Fatjeriyah; Muhammad Agus Muljanto (International Journal of Social, Economic, and Business, 2026)
This research evaluates the recommendatory authority of the SidoarjoRegency Election Supervisory Body (Bawaslu) in addressing neutralityviolations involving twelve village heads in Buduran District during the 2024General Election. While Bawaslu procedurally performed its functions withprofessional rigor, a significant asymmetry exists between the burden ofmaterial evidence and the restrictive nature of sanctioning enforcement.Grounded in the policy evaluation framework of Bridgman and Davis (2000),comprising input, process, output, and outcome indicators. This descriptivequalitative study identifies a "regulatory escape" from the Election Law to theVillage Law, which inadvertently diminishes legal substance. The resultsshow that the "process" indicator follows the rules of due process of law, butthe "outputs" turn into nothing more than symbolic administrativepunishments. Consequently, the purely recommendatory nature of thisauthority fails to produce a deterrent effect, necessitating regulatoryamendments to empower Bawaslu with independent executorial mandates.